Serum potassium changes due to concomitant ACEI/ARB and spironolactone therapy: A systematic review and meta-analysis. (20th May 2021) - Villa-Zapata, Lorenzo; Carhart, Briggs S; Horn, John R; Hansten, Philip D; Subbian, Vignesh; Gephart, Sheila; Tan, Malinda; Romero, Andrew; Malone, Daniel C
Abstract: Purpose: To provide evidence of serum potassium changes in individuals taking angiotensin-converting enzyme inhibitors (ACEIs) and/or angiotensin receptor blockers (ARBs) concomitantly with spironolactone compared to ACEI/ARB therapy alone. Methods: PubMed, Embase, Scopus, and Web of Science were searched for studies including exposure to both spironolactone and ACEI/ARB therapy compared to ACEI/ARB therapy alone. The primary outcome was serum potassium change over time. Main effects were calculated to estimate average treatment effect using random effects models. Heterogeneity was assessed using Cochran's Q and I 2 . Risk of bias was assessed using the revised Cochrane risk of bias tool. Results: From the total of 1, 225 articles identified, 20 randomized controlled studies were included in the meta-analysis. The spironolactone plus ACEI/ARB group included 570 patients, while the ACEI/ARB group included 547 patients. Treatment with spironolactone and ACEI/ARB combination therapy compared to ACEI/ARB therapy alone increased the mean serum potassium concentration by 0.19 mEq/L (95% CI, 0.12-0.26 mEq/L), with intermediate heterogeneity across studies ( Q statistic = 46.5, P = 0.004; I 2 = 59). Sensitivity analyses showed that the direction and magnitude of this outcome did not change with the exclusion of individual studies, indicating a high level of reliability. Reporting risk of bias was low for 16 studies (80%), unclear for 3 studies (15%) and high for 1 study (5%). Conclusion: Treatment with spironolactone in combination with ACEI/ARB therapy increases the mean serum potassium concentration by less than 0.20 mEq/L compared to ACEI/ARB therapy alone. However, serum potassium and renal function must be monitored in patients starting combination therapy to avoid changes in serum potassium that could lead to hyperkalemia.